Unfavourable risk factor control after coronary events in routine clinical practice. Issue 1 (December 2017) - Sverre, Elise; Peersen, Kari; Husebye, Einar; Gjertsen, Erik; Gullestad, Lars; Moum, Torbjørn; Otterstad, Jan; Dammen, Toril; Munkhaugen, John
Abstract Background Risk factor control after a coronary event in a recent European multi-centre study was inadequate. Patient selection from academic centres and low participation rate, however, may underscore failing risk factor control in routine clinical practice. Improved understanding of the patient factors that influence risk factor control is needed to improve secondary preventive strategies. The objective of the present paper was to determine control of the major risk factors in a coronary population from routine clinical practice, and how risk factor control was influenced by the study factors age, gender, number of coronary events, and time since the index event. Methods A cross-sectional study determined risk factor control and its association with study factors in 1127 patients (83% participated) aged 18-80 years with acute myocardial infarction and/or revascularization identified from medical records. Study data were collected from a self-report questionnaire, clinical examination, and blood samples after 2-36 months (median 16) follow-up. Results Twenty-one percent were current smokers at follow-up. Of those smoking at the index event 56% continued smoking. Obesity was found in 34%, and 60% were physically inactive. Although 93% were taking blood-pressure lowering agents and statins, 46% were still hypertensive and 57% had LDL cholesterol >1.8 mmol/L at follow-up. Suboptimal control of diabetes was found in 59%. The patients failed on average to control three of the six major risk factors, and patients with >1 coronary events (p < 0.001) showed the poorest overall control. A linear increase in smoking (p < 0.01) and obesity (p < 0.05) with increasing time since the event was observed. Conclusions The majority of coronary patients in a representative Norwegian population did not achieve risk factor control, and the poorest overall control was found in patients with several coronary events. New strategies for secondary prevention are clearly needed to improve risk factor control. Even modest advances will provide major health benefits. Trial registration Registered at ClinicalTrials.gov (IDNCT02309255 ).